Penerapan Sistem Kendali Otomatis WLC pada Pengelolaan Air Bersih di PDAM Lamongan - Ulul Imi; Eko Wahyu Santoso; Abdur Rohman Wakhid; Gading Wilda Aniriani; Fajar Dwi Kurniawan; Nuril Akhyar Kusuma Wardana (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to improve the effectiveness of clean water distribution management through the implementation of a Water Level Control (WLC) system as an automatic control for water pumps and three-phase motors at a regional drinking water supply company in Lamongan. The methods employed include field observation, problem identification, system design and implementation, as well as periodic evaluation of system performance. The activity focuses on the water treatment unit by conducting control and monitoring of operational parameters such as frequency (Hz), pump pressure, and flow stability to ensure optimal water distribution according to consumer needs. The results indicate that the implementation of the WLC system enhances operational efficiency, minimizes human error, and supports more structured and sustainable equipment maintenance. In addition, this activity contributes to improving the knowledge and technical skills of personnel in operating, monitoring, and maintaining automated control systems. In managing automation-based technology in a professional and independent manner, human resource capacity is strengthened, while the quality of clean water services is also improved through this community service program.